Two-point fixation enhanced the outcome of laparoscopy-assisted ventriculoperitoneal shunt in adult patients with hydrocephalus: a retrospective study - Wu, Jing-Nan; Zhou, Yu-Jie; Wang, Lei; Gan, Jin-Lu; Wang, Jian; Zhao, Hong-Yang; Lei, De-Qiang (Frontiers in Surgery, 2023)
Objective In patients with hydrocephalus, laparoscopy significantly improved ventriculoperitoneal shunt (VPS) outcomes. However, abdominal complications still occur, which require revision surgeries. In this study, we aimed to examine whether laparoscopy-assisted VPS with two-point fixation (LAVPS-TPF) has better outcomes than those of VPS (open-VPS) and laparoscopy-assisted VPS with no fixation (LAVPS-NF). Methods We retrospectively reviewed clinical records of 105 open-VPS, 40 LAVPS-NF, and 49 LAVPS-TPF cases from 2015 to 2020. Data including body mass index, etiology, abdominal surgery history, Glasgow coma scale (GCS), operation time, in-hospital days, shunt failure, complications, and modified Rankin scores were analyzed, as well as subgroups of patients with history of abdominal surgery, GCS scores, and revision surgeries. Results The LAVPS-TPF group demonstrated decreased shunt failure rates at 12 months (2.04%) compared to those of the open-VPS group (14.29%, P = 0.020) and reduced abdominal shunt-related complications (P = 0.004 vs. open-VPS and LAVPS-NF) and shunt revisions. In the LAVPS-TPF group with abdominal history (n = 51), 12-month shunt failure rates (P = 0.020 vs. open-VS), repair frequency (P = 0.020 vs. open-VS), and abdominal complications (P = 0.003 and 0.006 vs. open-VS and LAVPS-NF) were reduced. In the LAVPS-TPF group with GCS scores of 13–15 (n = 152), shunt failure rates at 12 months, abdominal complications, and revision frequency were decreased (P < 0.05 vs. other groups). Compared to the LAVPS-NF group, neurological complications were also reduced (P = 0.001). Among revision surgeries (n = 28), fixed shunts resulted in improved shunt survival rates at 12 months, reduced abdominal complications, and secondary revisions (P < 0.05). Moreover, a more optimal recovery without neurological sequelae was achieved by shunt fixation than that by LAVPS-NF (P < 0.01). Conclusions LAVPS-TPF significantly improved shunt survival rates at 12 months and reduced the incidence of abdominal shunt-related complications compared to open-VPS and LAVPS-NF, especially in patients with history of abdominal surgery, higher GCS scores, and revision surgeries. However, further studies are required to confirm these benefits.